Treating Depression With Tai Chi: State of the Art and Future Perspectives - Kong, Jian; Wilson, Georgia; Park, Joel; Pereira, Kaycie; Walpole, Courtney; Yeung, Albert (Frontiers in Psychiatry, 2019)
Major depressive disorder (MDD) is one of the most prevalent mental illnesses in America. Current treatments for MDD are unsatisfactory given high non-response rates, high relapse rates, and undesirable side effects. Accumulating evidence suggests that Tai Chi, a popular mind-body intervention that originated as a martial art, can significantly regulate emotion and relieve the symptoms of mood disorders. In this article, we first examine a number of clinical trials that implemented Tai Chi as a treatment for depression. Then, we explore several mechanisms by which Tai Chi may alleviate depressive symptoms, hypothesizing that the intervention may modulate the activity and connectivity of key brain regions involved in mood regulation, reduce neuro-inflammatory sensitization, modulate the autonomic nervous system, and regulate hippocampal neurogenesis. Finally, we discuss common challenges of the intervention and possible ways to address them. Specifically, we pose developing a simplified and tailored Tai Chi protocol for patients with depression, comparatively investigating Tai Chi with other mind-body interventions such as yoga and Baduanjin, and developing new mind-body interventions that merge the advantages of multiple mind-body exercises.